Cysteine Thioesters as Myelin Proteolipid Protein Analogues to Examine the Role of Butyrylcholinesterase in Myelin Decompaction - Pottie, Ian R. (American Chemical Society, 2010)
[Image: see text] Multiple sclerosis (MS) is a neuroinflammatory and neurodegenerative disorder involving demyelination, axonal transection, and neuronal loss in the brain. Recent studies have indicated that active MS lesions express elevated levels of butyrylcholinesterase (BuChE). BuChE can hydrolyze a wide variety of esters, including fatty acid esters of protein. Proteolipid protein (PLP), an important transmembrane protein component of myelin, has six cysteine residues acylated, via thioester linkages, with fatty acids, usually palmitic, that contribute to the stability of myelin. Experimental chemical deacylation of PLP has been shown to lead to decompaction of myelin. Because of elevated levels of BuChE in active MS lesions and its propensity to catalyze the hydrolysis of acylated protein, we hypothesized that this enzyme may contribute to deacylation of PLP in MS, leading to decompaction of myelin and contributing to demyelination. To test this hypothesis, a series of increasing chain length (C2−C16) acyl thioester derivatives of N-acetyl-l-cysteine methyl ester were synthesized and examined for hydrolysis by human cholinesterases. All N-acetyl-l-cysteine fatty acyl thioester derivatives were hydrolyzed by BuChE but not by the related enzyme acetylcholinesterase. In addition, it was observed that the affinity of BuChE for the compound increased the longer the fatty acid chain, with the highest affinity for cysteine bound to palmitic acid. This suggests that the elevated levels of BuChE observed in active MS lesions could be related to the decompaction of myelin characteristic of the disorder.